Effect of salinity on morpho-physiological traits at reproductive stages of Oryza sativa - Sultana, S; Sagar, A; Mia, MA; Kabir, MH; Shabi, TH; Dhar, M; Hossain, AKMZ (Progressive Agriculture, 2022)
Soil salinity is one of the most adverse environmental problems which restricts crop yield. Salinity affects rice plants very badly from germination to its maturity. Therefore, a pot experiment was conducted to study the salinity tolerance of rice genotypes viz. SAL655, STL15, PBRC37, Binadhan-8 and BRRI dhan28. The plants were grown under four salinity levels (0, 6, 9 and 12 dSm−1). Plant height, total number of green leaves hill−1, root dry weight, stem dry weight, total dry weight per hill, root shoot ratio was found to be decreased gradually with gradual increase in salinity levels as compared to the control. The genotype Binadhan-8 and PBRC37 showed the better performance in respect of all the parameters than other genotypes. Therefore, Binadhan-8 and PBRC37 were found more tolerant than other genotypes to salt stress. Progressive Agriculture 32 (2): 117-126, 2021